The Croatian Courses for the Joint European MA "Migrationa and Intercultural relations" - Mesić, Milan, sociolog (2008)
The presentation of the four Croatian courses to be included in the Joint European MA "Migration and Intercultural Relations": Controversies over Multiculturalism, Intercultural Education, Diaspora and Transnationalism, Peace and Conflict in Multiethnic Settings.
Projekt MZOS
ENG